Keratin 19 (Krt19) is a novel marker gene for epicardial cells - Xu, Juan; Deng, Yiting; Li, Guang (Frontiers in Genetics, 2024)
Epicardial cells regulate heart growth by secreting numerous growth factors and undergoing lineage specification into other cardiac lineages. However, the lack of specific marker genes for epicardial cells has hindered the understanding of this cell type in heart development. Through the analysis of a cardiac single cell mRNA sequencing dataset, we identified a novel epicardial gene named Keratin 19 (Krt19). Further analysis of the expression patterns of Krt19 and Wt1, a well-known epicardial gene, revealed their preferences in major cardiac cell types. Using lineage-tracing analysis, we analyzed Krt19-CreER labeled cells at multiple time windows and found that it labels epicardial cells at both embryonic and neonatal stages. Furthermore, we studied the function of epicardial cells using a diphtheria toxin A chain (DTA)-based cell ablation system. We discovered that Krt19-CreER labeled cells are essential for fetal heart development. Finally, we investigated the function of Krt19-CreER and Wt1-CreER labeled cells in neonatal mouse development. We observed that the Krt19-CreER; Rosa-DTA mice displayed a smaller size after tamoxifen treatment, suggesting the potential importance of Krt19-CreER labeled cells in neonatal mouse development. Additionally, we found that Wt1-CreER; Rosa-DTA mice died at early stages, likely due to defects in the kidney and spleen. In summary, we have identified Krt19 as a new epicardial cell marker gene and further explored the function of epicardial cells using the Krt19-CreER and Wt1-CreER-mediated DTA ablation system.